Black carbon radiative forcing over the Tibetan Plateau. Issue 22 (25th November 2014) - He, Cenlin; Li, Qinbin; Liou, Kuo‐Nan; Takano, Yoshi; Gu, Yu; Qi, Ling; Mao, Yuhao; Leung, L. Ruby
Abstract We estimate the snow albedo forcing and direct radiative forcing (DRF) of black carbon (BC) in the Tibetan Plateau using a global chemical transport model in conjunction with a stochastic snow model and a radiative transfer model. The annual mean BC snow albedo forcing is 2.9 W m−2 averaged over snow‐covered plateau regions, which is a factor of 3 larger than the value over global land snowpack. BC‐snow internal mixing increases the albedo forcing by 40–60% compared with external mixing, and coated BC increases the forcing by 30–50% compared with uncoated BC aggregates, whereas Koch snowflakes reduce the forcing by 20–40% relative to spherical snow grains. The annual BC DRF at the top of the atmosphere is 2.3 W m−2 with uncertainties of −70–85% in the plateau after scaling the modeled BC absorption optical depth to Aerosol Robotic Network observations. The BC forcings are attributed to emissions from different regions.